Anti-oxidant, Anti-inflammatory and Anti-Atherosclerotic Activity of Bioactive Peptide HPAEDR Isolated from Catla catal Muscle on LPS Induced Inflammation on 246.7RAW Macrophage Cells and HCF Induced Hyperlipidemic Zebrafish Larvae - Sabarinathan Sethuramalingam; Revathy Leena Ravi; Janet Rani Rajiah (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2022)
A muscle wasdissected from the Catla catlafish and enzyme hydrolysis was done using various digestive enzymes such as pepsisn, protease, papine, trypsin and alcalase at verity of time intervals (0th, 3rd, 6th, 9th and 12th) hour respectively. Followed by, the amino acid composition was identified and the confirmative assays such as, the anti-oxidant assays (DPPH and Hydroxy radical scavenging activity) and anti-inflammatory assays (HRBC and AD) were done for various peptide hydrolysate. The active hr was identified as 9th hr alcalase hydrolysate which was purified through Ultrafiltration (>30 kDa, 30-10 kDa, 10-3 kDa and <3 kDa). These fractions were again studied for its anti-oxidant and anti-inflammatory activity. Based on the results obtained, the active fraction was identified as 10-3kDa which was further purified and identified using Gel filtration chromatography and LC-MS/MS as HPAEDR (723.76 Da). Further, for in vitro and in vivo studies the peptide derived from CCM was synthetically designed with 98% purity (PhtdPeptides Co., Ltd. Zhemgzhou, China). Additionally, the physiochemical properties (Solubility, emulsifying properties and foaming properties) of these fraction was studied. Finally, the purified fraction was tested for in vitro activity through cell viability, COX-2 production, NO production and TNF-Î± production. Moreover, the in vivo protective effect is tested on Zebrafish larvae. The results suggest that the active purified peptide fraction isolated from Catla catla muscle has a strong natural anti-oxidant, anti-inflammatory and cholesterol reduction activity which can be used in functional foods and pharmaceuticals.